Staphylococcus aureus planktonic but not biofilm environment induces an IFN-β macrophage immune response via the STING/IRF3 pathway - Seebach, Elisabeth; Sonnenmoser, Gabriele; Hieke-Kubatzky, Katharina (Virulence, 2023)
Chronic implant-related bone infections are a severe complication in orthopaedic surgery. Biofilm formation on the implant impairs the immune response, leading to bacterial persistence. In a previous study, we found that Staphylococcus aureus (SA) induced interferon regulatory factor 3 (IRF3) activation and Ifnb expression only in its planktonic form but not in the biofilm. The aim of this study was to clarify the role of the stimulator of interferon genes (STING) in this process. We treated RAW 264.7 macrophages with conditioned media (CM) generated from planktonic or biofilm cultured SA in combination with agonists or inhibitors of the cyclic GMP-AMP synthase (cGAS)/STING pathway. We further evaluated bacterial gene expression of planktonic and biofilm SA to identify potential mediators. STING inhibition resulted in the loss of IRF3 activation and Ifnb induction in SA planktonic CM, whereas STING activation induced an IRF3 dependent IFN-β response in SA biofilm CM. The expression levels of virulence-associated genes decreased during biofilm formation, but genes associated with cyclic dinucleotide (CDN) synthesis did not correlate with Ifnb induction. We further observed that cGAS contributed to Ifnb induction by SA planktonic CM, although cGAS activation was not sufficient to induce Ifnb expression in SA biofilm CM. Our data indicate that the different degrees of virulence associated with SA planktonic and biofilm environments result in an altered induction of the IRF3 mediated IFN-β response via the STING pathway. This finding suggests that the STING/IRF3/IFN-β axis is a potential candidate as an immunotherapeutic target for implant-related bone infections.